An empirical research study on deluging quackery outlets across the Sindh, Pakistan and propositions to deal with confounding factors of rising quackery - Khan, Rehan; Mustufa, Mouhammad Ayaz (Journal of the Pakistan Medical Association, 2022)
Objective: To estimate the prevalence of medical quackery, to identify the confounding factors of the rising trend, and suggest possible ways to eliminate the menace. Method: This empirical study was conducted from July 2019 to June 2020 in six divisions of the Sindh province of Pakistan, and comprised field inspection reports and data collection based on healthcare establishments’ physical inspection, verification, and action on non-compliant units. Data was qualitatively and quantitatively analysed. Results: Of the 3,063 healthcare establishments, 568(18%) were visited in Larkana, 641(21%) in Shaheed Benazirabad (SBA), 527(17%) in Mirpurkhas, 700(23%) in Hyderabad, 110(4%) in Sukkur, and 517(17%) in Karachi. Overall, 2,152(70%) outlets were shuttered and fined for violating anti-quackery laws, while 911(30%) were issued warning notices. Conclusion: The healthcare system in the Sindh province was found to be struggling, with quackery continuing to proliferate. Key Words: Healthcare quackery, Propositions, Sociological significance.